The Effect of Coconut Fiber Powder (Cocopeat) Planting Media and KCl Fertilizer on the Growth and Yield of Queen Cucumber (Cucumis sativus L. var. Syakira) in Polybags - ramadhan, teguh adhetya; Sugiono, Darso; Pirngadi, Kasdi (Peneliti.net, 2026)
Cucumber (Cucumis sativus L.) is a horticultural plant from the Cucurbitaceae or pumpkin family. Cultivating cucumber plants in polybags is one way to plant in limited land. The aint of study to obtain the best cocopeat and KCl fertilizer planting media for the production of cucumber. The experiment was conducted in Cimekar Village, Cileunyi Sub District, Bandung District from October to December 2024. The research method was used an experimental method using a single factor Randomized Block Design (RBD) consisting of 12 treatments with 3 replications, so there were 36 experimental units. Treatment factors consist of A (0 g Cocopeat + 0 g KCl fertilizer/polybag), B (0 g Cocopeat + 10 g KCl fertilizer/polybag), C (0 g Cocopeat + 15 g KCl fertilizer/polybag), D (0 g Cocopeat + 20 g KCl fertilizer/polybag), E (500 g Cocopeat + 0 g KCl fertilizer/polybag), F (500 g Cocopeat + 10 g KCl fertilizer/polybag), G (500 g Cocopeat + 15 g KCl fertilizer/polybag), H (500 g Cocopeat + 20 g KCl fertilizer/polybag), I (1000 g Cocopeat + 0 g KCl fertilizer/polybag), J (1000 g Cocopeat + 10 g KCl fertilizer/polybag), K 1000 g Cocopeat + 15 g KCl fertilizer/polybag), L (1000 g Cocopeat + 20 g KCl Fertilizer/polybag). The results of the experiment showed that the L treatment (1000 g Cocopeat + 20 g KCl fertilizer/polybag) had a significant effect on plant height at the age of 42 dap, leaf area, fruit weight at the age of 62 dap, and total fruit weight.